Strengthening Cybersecurity for Patient Data Protection in Europe - Robin van Kessel; Madeleine Haig; Elias Mossialos (Journal of Medical Internet Research, 2023)
The health care sector experiences 76% of cybersecurity breaches due to basic web application attacks, miscellaneous errors, and system intrusions, resulting in compromised health data or disrupted health services. The European Commission proposed the European Health Data Space (EHDS) in 2022 to enhance care delivery and improve patients’ lives by offering all European Union (EU) citizens control over their personal health data in a private and secure environment. The EU has taken an important step in homogenizing the health data environment of the European health ecosystem, although more attention needs to be paid to keeping the health data of EU citizens safe and secure within the EHDS. The pooling of health data across countries can have tremendous benefits, but it may also become a target for cybercriminals or state-sponsored hackers. State-of-the-art security measures are essential, and the current EHDS proposal lacks sufficient measures to warrant a cybersecure and resilient environment.